First serological evidence of hantavirus infection in humans from the Orinoquia region of Colombia (2016)
Hantaviruses cause a significant number of human illnesses, making them a global public health threat. Approximately 150,000–200,000 patients with hemorrhagic fever with renal syndrome (HFRS) are hospitalized each year throughout the world. On average, approximately 200 cases of hantavirus pulmonary syndrome (HPS) per year are reported in the Americas, and although the number of cases is much smaller in number than that of HFRS, its average case fatality is about 40%.